2016
DOI: 10.1111/obr.12454
|View full text |Cite
|
Sign up to set email alerts
|

Eating and arterial endothelial function: a meta‐analysis of the acute effects of meal consumption on flow‐mediated dilation

Abstract: Given that endothelial dysfunction precedes atherosclerotic cardiovascular disease, exploring the parameters that modify postprandial flow-mediated dilation (FMD) is important for public health. The objectives of the study are to estimate the population effect of meal ingestion on FMD and to determine how the effect varied based on patient characteristics and modifiable methodological features. Articles published before June 2015 were located using MEDLINE, PubMed and Web of Science. One hundred fifty-four eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 65 publications
(79 reference statements)
1
41
1
Order By: Relevance
“…Thom and colleagues suggested in their recent meta-analysis involving 78 acute studies that the intake of a single meal significantly decreased postprandial FMD values after 1, 2 and 3 h in most, but not in all studies [6]. Heterogeneity in outcomes between studies was observed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thom and colleagues suggested in their recent meta-analysis involving 78 acute studies that the intake of a single meal significantly decreased postprandial FMD values after 1, 2 and 3 h in most, but not in all studies [6]. Heterogeneity in outcomes between studies was observed.…”
Section: Discussionmentioning
confidence: 99%
“…NO is a key determinant of endothelial function, since it exerts important vasodilatory, anti-inflammatory, antithrombotic, anti-proliferative, and anti-adhesive effects [2,4]. It has been hypothesized that meal ingestion as well as meal composition may change NO bioavailability [5][6][7]. Since we spend most time of the day in the postprandial state, repeated reductions in NO bioavailability caused by meal consumption may thus contribute to the development of CVD [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the flow-mediated or acetylcholine-induced vasodilatation is associated with nitric oxide (NO) released by endothelium, which is one of sensitive index of endothelium-dependent vasodilation. Clinical studies found that the postprandial rapid rise in serum TG levels after a high-fat meal was significantly related to endothelial dysfunction via evaluating the impairment in flow-mediated vasodilatation [ 55 ]. It has also been shown that the remnant lipoprotein contributes to the impairment of endothelium-dependent vasomotor function in human coronary arteries [ 56 ].…”
Section: The Possible Mechanism Of Trls Atherogenicitymentioning
confidence: 99%
“…FMD is predominately mediated by the release of nitric oxide (NO), a gaseous compound with antiadhesive, antithrombotic, and vasodilatory properties (Joyner and Green, 2009 ). The effect of acute feeding has been well summarized (Thom et al, 2016 ). Both fat- and carbohydrate-rich foods generally regarded as healthful have not been shown to reduce FMD (e.g., walnuts or oatmeal) (Brock et al, 2006 ; Cortes et al, 2006 ; Karatzi et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%